2015
DOI: 10.1016/j.immuni.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4-Neutrophil Elastase Axis Drives Neutrophil Reverse Transendothelial Cell Migration In Vivo

Abstract: SummaryBreaching endothelial cells (ECs) is a decisive step in the migration of leukocytes from the vascular lumen to the extravascular tissue, but fundamental aspects of this response remain largely unknown. We have previously shown that neutrophils can exhibit abluminal-to-luminal migration through EC junctions within mouse cremasteric venules and that this response is elicited following reduced expression and/or functionality of the EC junctional adhesion molecule-C (JAM-C). Here we demonstrate that the lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
249
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(274 citation statements)
references
References 50 publications
11
249
0
4
Order By: Relevance
“…38,39 Furthermore, S100A9 itself has been shown to attract macrophages 40 ; therefore, S100A9 deposited at the central area of granulomas may serve to recruit macrophages and activate them continuously via receptor for advanced glycation end products and TLR to produce proinflammatory cytokines, such as tumor necrosis factor-a, interleukin-1b, and interleukin-6, as well as chemokines, including macrophage inflammatory protein-1a and monocyte chemoattractant protein-1. 22 The prolonged exposure of macrophages to these highly proinflammatory conditions may lead to their transformation into epithelioid cells and multinucleated giant cells.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Furthermore, S100A9 itself has been shown to attract macrophages 40 ; therefore, S100A9 deposited at the central area of granulomas may serve to recruit macrophages and activate them continuously via receptor for advanced glycation end products and TLR to produce proinflammatory cytokines, such as tumor necrosis factor-a, interleukin-1b, and interleukin-6, as well as chemokines, including macrophage inflammatory protein-1a and monocyte chemoattractant protein-1. 22 The prolonged exposure of macrophages to these highly proinflammatory conditions may lead to their transformation into epithelioid cells and multinucleated giant cells.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, excessive LTB4 induced presentation of neutrophil elastase on CD11b, JAM-C degradation, and subsequent reverse transmigration (Figure 2). 27 Neutrophils undergoing reverse transmigration exhibited a proinflammatory phenotype characterized by a high ICAM-1 expression. 28 Interestingly, ICAM-1 high neutrophils were found in distant organs after ischemia/reperfusion or LTB4 infusion, suggesting a potential implication in the systemic propagation of inflammation.…”
Section: Transcriptional Plasticity: Numbers Mattermentioning
confidence: 99%
“…28 Interestingly, ICAM-1 high neutrophils were found in distant organs after ischemia/reperfusion or LTB4 infusion, suggesting a potential implication in the systemic propagation of inflammation. 27,28 Overall, reverse transmigration prolongs neutrophil lifespan and modulates their phenotype and function, thereby contributing to neutrophil heterogeneity.…”
Section: Transcriptional Plasticity: Numbers Mattermentioning
confidence: 99%
“…LTB4 binds with high affinity to its G protein-coupled receptor, LTB4R1 (also known as BLT1) (24). After specifically binding to LTB4R1, LTB4 exerts robust effects to promote leukocyte infiltration into various tissues and regulates proinflammatory cytokine production (25)(26)(27)(28)(29). Previous studies have demonstrated effects of the LTB4/LTB4R1 axis on recruitment and activation of macrophages in the context of obesity (30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%